Evaluation of Albazia chinensis as Tannins Source for In Vitro Methane Production Inhibitor Agents Sheep Rumen Liquor - Anas, Muhsin, Al (2015)
ABSTRACT: The objective of this study was to investigate the effect of Albazia chinensis as a source of tannin on in vitro methane production and rumen parameters. Two sheeps were used as donor of rumen microbes. Four experimental diets (grass:concentrat, 60:40) with addition of Albazia chinensis leaves equal to tannin level of 0%, 2%, 4% and 6% based on dry matter (DM) were used as substrate for in vitro fermentation by Menke and Steingass gas production method for 48 hours of incubation. Methane production, DM and organic matter (OM) digestibility, and parameters of rumen fermentation were measured at the end of incubation. Data obtained were analyzed by one way analysis of variance (ANOVA) continued by DMRT. The addition of Albazia chinensis leaves decreased (P<0.01) DM and OM digestibility with increasing of tannin level. Moreover, the treatment also decreased methane production. The significant decreasing occured at tannin level of 6%. The addition of tannin did not affect (P>0.05) number of protozoa, microbial proteins, ammonia, VFA and pH. It could be concluded that the addition of Albazia chinensis equal to tannin level of 6% is the optimal level to reduce methane production without any negative effects on rumen fermentation parameters. Keywords: Methane, Tannin, Albazia chinensis, Sheep, In vitro